2012
DOI: 10.1080/00207594.2012.669481
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial wellbeing in the Central and Eastern European transition: An overview and systematic bibliographic review

Abstract: This paper presents the results of a systematic review of literature on the psychosocial wellbeing of populations in Central and Eastern Europe during the transition period subsequent to the fall of the SovietBloc. A revision of research addressing emotional wellbeing trends in this period and theoretical models was carried in order to verify their validity in the analysis of empirical studies. Hence, a systematic bibliographic review was conducted, aiming to find possible subjective mediators between social v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Therefore, it remains unclear whether extrinsic aspirations per se and, more importantly, general causality orientations other than autonomy can produce psychological well-being in certain social and cultural contexts (see Ryan & Deci, 2001 on the antecedents of well-being). In a bibliographic review, Eiroa Orosa (2013) reported that locus of control, perceived control, and self-efficacy beliefs, which are conceptually related to autonomy orientation, only partially explained the impact of macrosocial changes and psychological well-being in Central and Eastern European countries. Our fourth research question centered on the relationship of autonomy, controlled, and impersonal causality orientations to psychological well-being in an understudied group: young European and Eurasian adults.…”
Section: Causality Orientations In Relation To Psychological Well-beingmentioning
confidence: 99%
“…Therefore, it remains unclear whether extrinsic aspirations per se and, more importantly, general causality orientations other than autonomy can produce psychological well-being in certain social and cultural contexts (see Ryan & Deci, 2001 on the antecedents of well-being). In a bibliographic review, Eiroa Orosa (2013) reported that locus of control, perceived control, and self-efficacy beliefs, which are conceptually related to autonomy orientation, only partially explained the impact of macrosocial changes and psychological well-being in Central and Eastern European countries. Our fourth research question centered on the relationship of autonomy, controlled, and impersonal causality orientations to psychological well-being in an understudied group: young European and Eurasian adults.…”
Section: Causality Orientations In Relation To Psychological Well-beingmentioning
confidence: 99%
“…[4][5][6], and general well-being indicators cf. [7,8]. In light of these findings the question arises: will post-socialist countries ever see eye to eye with Western European countries in societal trends?…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important in a rapidly changing postsocialist country like Hungary where societal processes may have an impact on the individual’s coping resources and behavioral decisions [30]. Despite that fact that frequencies of substance use in Hungary are still relatively greater than those from Western European countries [31], we know less about their background variables, e.g., motivations.…”
Section: Discussionmentioning
confidence: 99%
“…In a rapidly changing country like Hungary, all these changes may have an effect on coping resources and health decisions [29]. Few data are available for an understanding of these processes [30], although adolescent smoking and drinking are still higher in prevalence in Hungary and other Eastern European countries as compared with Western states [31]. For the present research we used a previously validated multidimensional motive measure to examine relations of four motive dimensions to smoking and drinking behavior.…”
Section: Introductionmentioning
confidence: 99%